Governance for Sustainability – Two Case Studies from Hungary - Pálné Kovács, Ilona; Varjú, Viktor (Discussion Papers, 2012)
The EU 6th Framework Programme entitled Governance for Sustainability (G-FORS) was aimed at the analysis of different governance and knowledge forms from the aspect of sustainability. In the recent paper two sustainability policies had been chosen to study the materialisation of them. The first is the new environmental policy of Strategic Environmental Assessment (SEA) while the second one is the Emission Trade Scheme (ETS) in Hungary. The main task in both cases was to investigate the following topics: how the environmental regulations and rules fit in the decision making processes, who are the most important actors of the decisions and how intensive and in which quality are those involved, what type of knowledge or cognition is necessary to enforce environmental interests? Regarding the SEA in Hungary in the investigated period of planning in 2006 (the period of preparation of plans for the 2007-13 period) - seeking out the national and regional level of planning as well - it can be said that the SEA can achieve adequate level of efficiency only if it is an integrated, internal part of the planning institution and procedure. While the open character of the action arena, the penetrability of organisational borders, the dominance of network elements and the expansion of learning opportunities could serve the sustainability, in our case the rigid/strict top down regulation, the knowledge integrated in the organisation seem to be the practicable paths. Analysing the ETS system regarding the 2005-2007 ETS period in Hungary the figure was similar. We can state that the policy was successful; however, having regarded the involved stakeholders in the process we can say that the top-down regulation could be detected here as well. The dominant form of knowledge was the economic knowledge driven by profit maximisation. Summing up the two cases it can be said the hereditary hierarchical governance mode and the non-integrated (only parallel appeared) environmental interest and knowledge could not contribute to the real sustainable policy materialisation and to the real environmental policy integration.